The souls of mixed folk : race, politics, and aesthetics in the new millennium - Elam, Michele (Stanford University Press, 2011)
The Souls of Mixed Folk examines representations of mixed race in literature and the arts that redefine new millennial aesthetics and politics. Focusing on black-white mixes, Elam analyzes expressive works-novels, drama, graphic narrative, late-night television, art installations-as artistic rejoinders to the perception that post-Civil Rights politics are bereft and post-Black art is apolitical. Reorienting attention to the cultural invention of mixed race from the social sciences to the humanities, Elam considers the creative work of Lezley Saar, Aaron McGruder, Nate Creekmore, Da.